2018
DOI: 10.1111/ene.13765
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychiatric phenotype in CACNA1A mutations: a retrospective single center study and review of the literature

Abstract: Neuropsychiatric manifestations are common in episodic CACNA1A disorders. In the case of otherwise unexplained developmental delay and a positive family history, CACNA1A mutations should be considered in the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
2
27
0
1
Order By: Relevance
“…Recently, a large case series of 23/44 patients (11/23 FHM1,10/23 EA2, 2/23 SCA6), investigated by a formal neuropsychological testing, predominantly showed figural memory, visuoconstructive abilities, and verbal fluency impairment. Furthermore, the study revealed that neuropsychological deficits were consistent with history of development delay of patients [19]. A case study carried out using a formal neuropsychological assessment reported an impairment of semantic fluency and of processing speed, and a mild executive dysfunction [18].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recently, a large case series of 23/44 patients (11/23 FHM1,10/23 EA2, 2/23 SCA6), investigated by a formal neuropsychological testing, predominantly showed figural memory, visuoconstructive abilities, and verbal fluency impairment. Furthermore, the study revealed that neuropsychological deficits were consistent with history of development delay of patients [19]. A case study carried out using a formal neuropsychological assessment reported an impairment of semantic fluency and of processing speed, and a mild executive dysfunction [18].…”
Section: Discussionmentioning
confidence: 57%
“…This co-occurrence in CACNA1A mutant patients has been associated with more severe outcome [16]. Many studies remarked in FHM1, EA2,and SCA6 patients the co-occurrence of behavioral and neuropsychological disorders but the investigations carried out with formal neuropsychological testing are scarce [17][18][19]. Recently, a large case series of 23/44 patients (11/23 FHM1,10/23 EA2, 2/23 SCA6), investigated by a formal neuropsychological testing, predominantly showed figural memory, visuoconstructive abilities, and verbal fluency impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Precise cognitive evaluations are the main contribution of our study. Recently, Indelicato et al . reported cognitive and behavioral features in a series of patients with CACNA1A mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Precise cognitive evaluations are the main contribution of our study. Recently, Indelicato et al 23 reported cognitive and behavioral features in a series of patients with CACNA1A mutations. However, the authors performed a retrospective analysis of data extracted from a database initially developed for another objective, therefore the protocol assessment of cognitive function was not uniform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation